Implementasi Reformasi Birokrasi, Kepemimpinan Transformasional, Pelatihan Dan Kompetensi Pegawai Terhadap Kinerja Pelayanan Di KPPBC Tipe Madya Bea Cukai Kediri - Mulyono, Hartoyo (Otonomi, 2022)
The purpose of this study was to determine the factors that influence service performance at KPPBC Type Madya Excise Kediri, measured by the variables of Bureaucratic Reform Implementation, Transformational Leadership, Training and Employee Competence on Service Performance. Data collection was carried out through distributing questionnaires to employees of the Kediri Excise Office of Intermediate Type KPPBC, either directly or indirectly. The sample used was 84 respondents. Data analysis in this study used multiple regression analysis with the help of SPSS version 20. The results of this analysis indicate that the variables, Transformational Leadership, Training and Competence of Employees have a positive and significant effect on Service Performance at KPPBC Intermediate Types of Excise, Kediri, Implementation of Bureaucratic Reform has no positive and significant effect on Service Performance at KPPBC Type Madya Excise Kediri.